Evaluation of various filter paper and reagent systems for the preservation of Newcastle disease virus RNA samples - Qaisieh Bajes Amjed Al; Ababneh Mustafa Mohammed-Khair; Al-Zghoul Mohammad Borhan F.; Alghizzawi Daoud Abed Alnaser; Aboomer Hebah Alaeddin (Journal of Veterinary Research, 2025)
The transport of Newcastle disease virus (NDV) specimens, isolates or purified RNA is traditionally performed at ultra-low temperatures using dry ice to prevent degradation. However, this method is costly and requires specialised packaging and stringent shipping conditions. The aim of this study is to evaluate existing products’ capacities to preserve NDV or its RNA under different conditions.